2021
DOI: 10.3390/ijms222212589
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Induces Apoptotic and Pyroptotic Cell Death via NLRP3 Inflammasome Activation in Rat Hepatocytes

Abstract: Leptin, a hormone that is predominantly produced by adipose tissue, is closely associated with various liver diseases. However, there is a lack of understanding as to whether leptin directly induces cytotoxic effects in hepatocytes as well as the mechanisms that are involved. Inflammasomes, which are critical components in the innate immune system, have been recently shown to modulate cell death. In this study, we examined the effect of leptin on the viability of rat hepatocytes and the underlying mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(55 reference statements)
0
4
0
1
Order By: Relevance
“…Maturation of cathepsin B leading to its enhanced secretion from lysosomes encourages direct interaction with NLRP3 inflammasomes and ultimately promotes its activation [42]. In recent years, the axis of autophagy and cathepsin B maturation has emerged as a crucial player in the modulation of inflammasome activation in different conditions [43,44].…”
Section: Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturation of cathepsin B leading to its enhanced secretion from lysosomes encourages direct interaction with NLRP3 inflammasomes and ultimately promotes its activation [42]. In recent years, the axis of autophagy and cathepsin B maturation has emerged as a crucial player in the modulation of inflammasome activation in different conditions [43,44].…”
Section: Proteasesmentioning
confidence: 99%
“…The most well-known among them are the adipokines, namely leptin and visfatin [59,60]. Leptin induces inflammasome activation in diverse cell types, including hepatocytes [43]. Androgens have been reported to stimulate inflammasome activation leading to hepatic fibrosis [61].…”
Section: Hormone-induced Hepatotoxicitymentioning
confidence: 99%
“…Leptin can modulate lipid metabolism in hepatocytes, resulting in hepatic steatosis [150]. A study has shown that leptin exerts direct hepatocyte pyroptosis via ROS production/ER stress/autophagy induction/ cathepsin B maturation/NLRP3 inflammasomes axis, leading to potential liver injury [151]. Moreover, leptin can also trigger hepatocyte pyroptosis through CD8 + T lymphocytes.…”
Section: Lipid Storage: Hypertrophic Adipocytes Induce Obese Adipocyt...mentioning
confidence: 99%
“…Среди основных периферических эффектов лептина стоит выделить разобщение окисления и фосфорилирования в жировой ткани, что приводит к липолизу и, как следствие, усилению выработки тепла [15,18]. Описано стимулирующее влияние лептина на процессы апоптоза в жировой ткани за счет высвобождения каспазозависимых белков и образования активных форм кислорода [19]. резистин Резистин -богатый цистеином пептид с молекулярной массой 12,5 кДа.…”
Section: лептинunclassified